Company reporting transparency and firm performance in Nigeria - Edogbanya, Adejoh; Kamardin, Hasnah (Asia Pacific Institute of Advanced Research (APIAR), 2016)
Transparency of companies’ activities with respect to board, financial and management of a firm and the relationship that exist between them is crucial because information disclosure solves the problem of information asymmetries and signaling of relevant material information to the stakeholders.This study examines the transparency and its relationship with performance of non-financial listed companies in Nigeria.The study adopts the panel data analysis (2010-2013) and relationship between transparency and firm performance.The research adopts the panel corrected standard errors (PCSEs) as a result of auto correlation and heterocadesticity in the model.The findings of the study shows research which further concludes that transparency of relevant information can lead to firm performance as shown by the significant relationship (positive with Tobin’s Q and negative with ROA) of transparency of board and transparency in financial have positive relationship with Tobin’s Q.The implication for this study is that a public limited company should practice full disclosure of material information and to disclose more than the statutory minimum requirements.